Evolution of European bison image and its implications for current species conservation - Samojlik Tomasz; Daszkiewicz Piotr; Fedotova Anastasia; Ričkienė Aurika; Cielemęcka Olga; Szczygielska Marianna (Public Library of Science, 2025)
Visual media are one of the fastest and most effective tools informing the public about conservation goals and convincing societies to support conservation actions. Similar mechanisms functioned in the past, only within a much longer time scale and different communication channels. We analyse the evolution of European bison’s depictions between 1500 and 1900 in the context of building public awareness of the species and its conservation needs. Experts evaluated the anatomical accuracy of thirty eight images of the species from the period analysed, and their conservation appeal was assessed by using an online survey of the general public. Existing knowledge and previous publications allowed authors to describe the development of the scientific knowledge about European bison in 1500–1900. By juxtaposing this with anatomical accuracy of depictions, a conclusion was reached that the accuracy of depictions was not directly linked to the state of knowledge about the species. In the survey, the public reception of the accuracy of historical pictures of European bison, as well as their potential to be used in conservation campaigns, was connected with subjective appeal of depicted animals. This lesson can be translated to modern conservation campaigns using mass media and global communication channels: popularization of knowledge on species of concern should be accompanied by appealing depictions of these species to strengthen public reception.